2012
DOI: 10.1177/0748233711433937
|View full text |Cite
|
Sign up to set email alerts
|

Proposed remedies for some developmental disorders

Abstract: Developmental disorders (DDs) are important leading cause of disability in developed countries and also in the United States. DDs are a group of individual conditions that result from abnormal nervous system development and cause altered function. They can begin at any time from prenatal to 22 years of age and the disability usually presents itself throughout a person's life time. Down syndrome, autism, neural tube defects, schizophrenia, cretinism, and attention-deficit hyperactivity disorder are among the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 129 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…The acquired data have shown that taking-in essential dietary supplements decreases the extent and frequency of symptoms in patients with mental disorders [23,31]. Diet is also likely to have an influence on genetic, hormonal, immunological, biochemical and neurodegenerative factors involved in depression [25,36].…”
Section: Selenium and Manganese In Depression -Preclinical And Clinicmentioning
confidence: 99%
“…The acquired data have shown that taking-in essential dietary supplements decreases the extent and frequency of symptoms in patients with mental disorders [23,31]. Diet is also likely to have an influence on genetic, hormonal, immunological, biochemical and neurodegenerative factors involved in depression [25,36].…”
Section: Selenium and Manganese In Depression -Preclinical And Clinicmentioning
confidence: 99%
“…Omega-3 fatty acids have several functions in the body and metabolism, exhibiting a disease protection factor due to their anti-inflammatory, antithrombotic, and anti-arteriosclerotic effects. Additionally, Omega-3 fatty acids act on the modulation of serotonin and allow for an increase of the availability of this neurotransmitter in the synaptic cleft, which is essential for neural functioning [ 17 , 18 , 19 ]. Changes in the action, availability and serum production of serotonin and dopamine are related to the pathophysiology of depression, although all the mechanisms involved are not elucidated [ 14 , 20 ].…”
Section: Introductionmentioning
confidence: 99%